Community and Society Collaborative Event Model at Karimba Fest 2024 Tanjung Belit, Riau - Isnu Hadi Sunarko; Nina Mistriani (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This research aims to develop a hexahelix collaborative event model for organizing Karimba Fest 2024 in Tanjung Belit, Riau. The research method uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and Focus Group Discussion (FGD). The results showed that collaboration involving the government, entrepreneurs, communities, independent institutions, media, and academics in planning, implementing, and evaluating events contributed to the successful organization of Karimba Fest 2024. The collaborative event model developed consists of stages: 1) identification of hexahelix potential and needs; 2) formation of collaborative work teams; 3) participatory event planning; 4) collaborative event implementation; and 5) participatory monitoring and evaluation. This research contributes a collaborative event model that can be applied in developing hexahelix-based tourism events with an impact on environmental and cultural preservation.